2019
DOI: 10.4103/jhrs.jhrs_168_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periodontal status among men undergoing infertility treatment

Abstract: Aims: It has been estimated that >30% of male infertility cases are of idiopathic etiology. Recent studies revealed a positive connection between periodontal pockets and sperm submotility, which proposes that periodontitis may have a role in male infertility and inadequate semen quality. The aim of the present investigation was to inspect the relationship between male fertility parameters and the periodontal status of male patients attending in vitro treatment (IVF) clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Pocket probing depth was considered in 13 studies, 14‐18,29‐36 level of clinical attachment was reported in 12 studies, 14‐18,29‐31,33,34,36,37 and bleeding on probing was reported in 6 studies 15‐17,30,33,34 . Of the 17 studies selected, only 4 considered the number of missing teeth 16,18,29,33 and 2 considered tooth mobility 16,36 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pocket probing depth was considered in 13 studies, 14‐18,29‐36 level of clinical attachment was reported in 12 studies, 14‐18,29‐31,33,34,36,37 and bleeding on probing was reported in 6 studies 15‐17,30,33,34 . Of the 17 studies selected, only 4 considered the number of missing teeth 16,18,29,33 and 2 considered tooth mobility 16,36 …”
Section: Resultsmentioning
confidence: 99%
“…Semen quality was evaluated in all studies using a seminogram (seminal fluid analysis) (Table 3). 16,17,29,30,38 The semen quality analysis was based on criteria defined by the World Health Organization (WHO) laboratory manual for the examination and processing of human semen (1999) 43 or (2010) 44 depending on the selected studies. A total of 728 patients from six retrospective studies 16,17,29,30,38,45 with a mean age of 33.45 years were included for investigating the relationship between periodontitis and semen quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations